РОЛЬ ЗАКЛАДІВ ВИЩОЇ ОСВІТИ У ВПРОВАДЖЕННІ ОСВІТИ ДЛЯ СТАЛОГО РОЗВИТКУ (ОСР). - Скиба, Вікторія Павлівна; Skyba, Viktoriia; Ганчук, Максим Миколайович; Hanchuk, Maksym; Аюбова, Ельнара Мусаібовна; Aiubova, Elnara (My University, 2024)
Higher Education Institutions (HEIs) play a fundamental role in the implementation of environmental education and the shift of educational paradigms within Education for Sustainable Development (ESD). HEIs are foundational in preparing the intellectual workforce for the country's development, as their primary functions focus on teaching, research, and the dissemination of information. HEIs not only contribute to the training of professionals across various sectors of the economy but also create, preserve, and transmit cultural and scientific heritage, which is essential in shaping societal values. ESD represents a modern process of lifelong learning and is an indispensable part of quality education.